2000
DOI: 10.1177/104346300012003003
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Being Asked

Abstract: A common phenomenon in social life is that some individuals help others and a few even risk their lives to benefit others, as in the case of those who helped Jews escape persecution in Nazi Europe. A few scholars single out motivations as the prime explanation of these rescue activities, yet concede that material opportunities, information, and other situational factors might have played a role. Their work, however, stops short of offering an account of the nature and importance of these factors. In this artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(4 citation statements)
references
References 24 publications
0
3
1
Order By: Relevance
“…Emerging from these analyses is a portrait of the Holocaust rescuers, or "Righteous Gentiles," that is different from the nonrescuers. In contrast to the view that rescuers are "ordinary people" for whom situational factors were often critical (Varese & Yaish, 2000), the rescuers whom we interviewed were quite distinctive. These Holocaust heroes exhibited high degrees of altruism and proactivity, and they are far more helpful than the nonrescuers many years after the Second World War and well into their older adulthood.…”
Section: Implications and Conclusioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Emerging from these analyses is a portrait of the Holocaust rescuers, or "Righteous Gentiles," that is different from the nonrescuers. In contrast to the view that rescuers are "ordinary people" for whom situational factors were often critical (Varese & Yaish, 2000), the rescuers whom we interviewed were quite distinctive. These Holocaust heroes exhibited high degrees of altruism and proactivity, and they are far more helpful than the nonrescuers many years after the Second World War and well into their older adulthood.…”
Section: Implications and Conclusioncontrasting
confidence: 71%
“…These survivor families recalled the bystanders as people who were not perpetrators or known informers and who "stayed out" of rescue activities. The bystanders interviewed here are people who reported that they offered no help even when they were asked for help (see Varese & Yaish, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, although Jews who were saved from the Nazi Holocaust were typically aided by people they knew, many rescuers were strangers. In the majority of such cases, the two were connected indirectly by an intermediary (Varese & Yaish 2000). More generally, studies of naturally occurring networks find that generosity decreases as the network distance between individuals increases, such that people are generous toward friends of friends, somewhat less so toward friends of friends of friends, and least generous toward more distal others or strangers (Apicella et al 2012, Baldassarri & Grossman 2013, Leider et al 2009.…”
Section: Distal and Indirect Effects Of Network Relations On Prosocia...mentioning
confidence: 99%
“…The uncertain environment during the pogroms meant that many neighbours declined to help, either voluntarily (in support of co-ethnics) or out of self-preservation – regardless of the nature of prior contact. Conversely, several engaged in rescue acts despite the risk to their lives, giving us reason to believe that humans are capable of more acts of rescue than are actually observed (Varese and Yaish, 2000).…”
Section: Discussionmentioning
confidence: 99%